A New Concept of Nature as a Foundation for Ethics: On the Relevance of Hans Jonas - Marcus Knaup; Hanna Hubenko; Galyna Iarmolovych (Філософія освіти, 2020)
The article is devoted to the bioethical reconstruction of the theoretical heritage of Hans Jonas (1903-1993) – a famous German and later American philosopher. Jonas showed that the study of ethics, namely the ethics of the living, should become an integral part of the formation of modern human, his complete education. He was one of the most fascinating thinkers of the twentieth century. He has presented groundbreaking works which are still the subject of serious discussion especially in the areas of ethics and philosophy of nature. In these publications he presents an in-depth philosophical reflection on the relationship between human beings and nature, as well as on the manner in which we approach our association with technology. Particularly in the light of possibilities presented by modern technology, Jonas was primarily interested in a new approach to the philosophy of nature as the basis, the foundation for an ethics of global responsibility. The article re-actualizes the thoughts and arguments of Jonas, which are especially relevant now, at the beginning of the XXI century. These include: the technique change the nature itself, not just human's attitude to nature; the technical sciences change a human being, the mathematization of nature leads to a change not only in human evaluation, but also in human value; critique of epiphenomenalism for underestimating mental states and identifying the non-reducibility of living creatures to its parts; the search for the potential of subjectivity in the realm of living creatures as a whole; reliance on the principle of responsibility as a way to ensure a future humanity as guaranteed, albeit limited in its capabilities. Educating a person on the basis of the principle of responsibility opens the possibility to take into account the interests of future generations and all living creatures, understanding that every person always was, is and will be a part of realm of these creatures. The philosophy of nature as such whole realm creates the preconditions and foundations for the ethics of responsibility as a postconventional universalist ethics. A new way of thinking in nature is the basis of ethics in the technological age: in addition to philosophy and science, the voices of religion, politics, education and the public sphere must also be heard to find answers to current life questions.